Understanding employment relations - Dundon, Tony; Rollinson, Derek (London : McGraw-Hill, 2011)
"Understanding Employment Relations examines introduces the fundamental theoretical and legal aspects of employment relations, and group of these in real-world practice. It provides an authoritative, in-depth analysis of Australia's unique regulatory environment, situating the rules that govern employment relations in historical, political and theoretical contexts. Combined with practical examples throughout, this analysis helps readers make sense of the day-to day practice of industrial relations. This book ensures that human resource students and future practitioners develop a comprehensive understanding of the latest laws and regulations, the roles of key players, and of the processes governing workplace relations."--Back cover.
Includes bibliographical references and index.
Keywords: Personnel management; Industrial relations; Work environment; Labor unions